2021
DOI: 10.1002/jsfa.11496
|View full text |Cite
|
Sign up to set email alerts
|

The anti‐obesity and gut microbiota modulating effects of taxifolin in C57BL/6J mice fed with a high‐fat diet

Abstract: BACKGROUND: Taxifolin is a natural dihydroflavonol found in many plants and health products. In the present study, its anti-obesity and gut microbiota modulating effects were studied. C57BL/6J mice were fed with a high-fat diet (HFD) supplemented with taxifolin (0, 0.5 and 1 mg mL −1 , respectively) in drinking water for 15 weeks. RESULTS: Taxifolin supplementation showed no influence on food and water intake. However, it decreased body weight gain, inhibited fat accumulation, and decreased total cholesterol a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 43 publications
0
20
0
Order By: Relevance
“…Thus, no clear significant differences between the F:B or B:F ratio and obesity status was found. In animal studies, the F:B ratio is considered a hallmark of obesity and is therefore used as an outcome to assess the effects of many anti-obesity dietary supplements [ 63 , 64 ] based on their capacity to modulate the gut microbiome by reducing the F:B ratio in the obese. Two systematic reviews [ 24 , 25 ] that included studies measuring the ratio by high-throughput sequencing methods and other methods, such as culture, flow cytometry, and qPCR, among others, found more studies that showed no statistically significant differences in the F:B ratio between obese and non-obese persons than others that did, which is in agreement with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, no clear significant differences between the F:B or B:F ratio and obesity status was found. In animal studies, the F:B ratio is considered a hallmark of obesity and is therefore used as an outcome to assess the effects of many anti-obesity dietary supplements [ 63 , 64 ] based on their capacity to modulate the gut microbiome by reducing the F:B ratio in the obese. Two systematic reviews [ 24 , 25 ] that included studies measuring the ratio by high-throughput sequencing methods and other methods, such as culture, flow cytometry, and qPCR, among others, found more studies that showed no statistically significant differences in the F:B ratio between obese and non-obese persons than others that did, which is in agreement with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that taxifolin relieved DSS-induced colitis by NF-κB signal way [ 26 ], and Su et al reported that taxifolin, which could improve the obesity symptoms, hepatic steatosis, and gut microbiota dysbiosis in HFD fed C57BL/6 mice [ 27 ]. However, no relevant studies have reported that taxifolin could relieve intestinal mucositis induced by DSS treatment by regulating intestinal flora.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, an increasing amount of research has shown that taxifolin regulates intestinal flora in the colon [ 26 ]. For example, taxifolin can treat metabolic disorders induced by obesity in rats via modulating intestinal flora [ 27 ]. Moreover, it was suggested that inflammation played a critical role in the pathological process of UC, and taxifolin protected DSS-induced UC by inhibiting the inflammatory response [ 26 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Desulfovibrionceae are sulfate reducing and lipopolysaccahride (LPS) producing bacteria promoting inflammation and obesity ( 100 , 101 ). In addition, members of Rikenella are also associated with obesity and gut epithelial injury ( 96 , 102 ). More importantly, these changes in the gut microbiome were highly predictive of subsequent protection from HFD-induced weight gain in female mice, while no such association was observed in male DHF-supplemented animals ( 38 ).…”
Section: Discussionmentioning
confidence: 99%